Pemimpin Perempuan dalam Sejarah Yogyakarta Hadiningrat dan Relevansinya terhadap UUK DIY - Al Wafi, Abdul Rohim; Rahtikawati, Yayan; Nurmila, Nina (STAINI Press, 2023)
Indonesia is a democratic country with a unitary state system and uses a republic form. This has been stated in Indonesia's main constitution, namely the 1945 Constitution. As a consequence of using the above system, Indonesia has several regions under it which have their own autonomy. One of the autonomy that exists in Indonesia is the special status attached to the province of Yogyakarta. The privileges of Yogyakarta have long been legitimized by related laws, namely Law Number 2 of 1948. Apart from that, the privileges of Yogyakarta have also been strengthened by institutionalizing the form of the Sultanate and standardizing the highest regulations for the area; paugeran, into national regulations, namely Law No. 13 of 2012. So this research focuses on the extent to which paugeran is accommodated by Law no. 13 of 2012, specifically on the aspect of female leaders. This research is an analytic normative research using two theoretical approaches, namely stipulative theory and genealogical theory. It was found that Law no. 13 of 2012 was unable to fully accommodate the paugeran owned by the Sultanate of Yogyakarta. This is evidenced by the existence of several nomenclatures that are not in line with paugeran. In fact, paugeran is the spirit and spirit of the formation of Law no. 13 of 2012